2023
DOI: 10.3390/plants12040944
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exogenous Auxin on Mesocotyl Elongation of Sorghum

Abstract: The length of sorghum mesocotyl plays a vital role in seed emergence from the soil, which is the foundation of healthy growth. In this study, we aimed to understand how exogenous auxin (IAA) promoted mesocotyl elongation of sorghum and its physiology mechanism. The results presented that exogenous IAA significantly promoted mesocotyl elongation in MS24B (short mesocotyl inbred line) by increasing the cell length, while with extra exogenous NPA (IAA inhibitor) application, the mesocotyl length presented a signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…In this study, the root length, seedling length, mesocotyl length, coleoptile length and the sum of the mesocotyl and coleoptile lengths of the maize inbred lines Qi319 and Zi330 under deep-sowing conditions all changed to varying degrees, among which mesocotyl elongation was the most significant. Studies have shown that exogenous IAA [ 24 ], GA 3 [ 25 ], BR, SL (strigolactone) [ 26 ], EBR (2,4-Epibrassinolide Solution) [ 27 ], etc., promote the elongation of mesocotyls under deep-sowing conditions. In this study, we found that exogenous SA significantly promoted the elongation of the mesocotyl, exogenous 6-BA significantly inhibited the elongation of the mesocotyl, and the SA–6-BA combined treatment also showed an inhibitory effect, but the inhibitory effect was weaker, indicating that there may be an interaction between these two hormones; exogenous SA partially alleviated the inhibitory effect of exogenous 6-BA on mesocotyl elongation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the root length, seedling length, mesocotyl length, coleoptile length and the sum of the mesocotyl and coleoptile lengths of the maize inbred lines Qi319 and Zi330 under deep-sowing conditions all changed to varying degrees, among which mesocotyl elongation was the most significant. Studies have shown that exogenous IAA [ 24 ], GA 3 [ 25 ], BR, SL (strigolactone) [ 26 ], EBR (2,4-Epibrassinolide Solution) [ 27 ], etc., promote the elongation of mesocotyls under deep-sowing conditions. In this study, we found that exogenous SA significantly promoted the elongation of the mesocotyl, exogenous 6-BA significantly inhibited the elongation of the mesocotyl, and the SA–6-BA combined treatment also showed an inhibitory effect, but the inhibitory effect was weaker, indicating that there may be an interaction between these two hormones; exogenous SA partially alleviated the inhibitory effect of exogenous 6-BA on mesocotyl elongation.…”
Section: Discussionmentioning
confidence: 99%
“…Jin Mengran et al 10 found that endogenous IAA and gibberellin (GA3) contents of Syringa villosa were significantly higher than that of the control after IAA treatment, while abscisic acid (ABA) content was significantly decreased. Liu Chang et al 11 showed that exogenous IAA significantly promoted mesocotyl elongation in MS24B (short mesocotyl autocotyledonous line) by increasing cell length. In MS24B, IAA treatment increased amylase activity to degrade starch into soluble sugars and hexokinase activity was increased to consume the increased soluble sugars to provide more energy.…”
Section: Introductionmentioning
confidence: 99%
“…The mesocotyl is a crucial organ located between the coleoptilar node and the basal part of the seminal root in sorghum seedlings [ 3 ]. The extension and division of mesocotyl cells are basic factors influencing mesocotyl elongation, and the extension of the mesocotyl cells seems more important [ 4 ]. Furthermore, selective loosening and remodeling of the cell walls is an important factor affecting mesocotyl elongation [ 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%